Characterization of Thermal Runaway of Lithium Ternary Power Battery in Semi-Confined Space - Hai Xu; Chenghao Hou; Po Hu; Yanhe Chen (Energies)
In some new energy aircraft powered by lithium-ion batteries (LIBs), the LIBs operate in semi-confined spaces. Therefore, studying the thermal runaway (TR) characteristics of LIBs in such spaces is significant to safety research of new energy aircraft. This paper investigated TR of LIBs in semi-confined space by using external heating, and compared it with the TR characteristics in open space in terms of behavior characteristics and temperature changes of lithium ternary power batteries in semi-confined spaces. The results show that the TR process of LIBs can be subdivided into seven different stages according to the TR characteristics of LIBs. Compared with the TR process of the LIB in open space, TR of the LIB in semi-confined space has an additional explosion stage. In terms of temperature, the maximum TR temperature of the LIB in open space is 708 °C, and the maximum heating rate is 72.3 °C/s, while the maximum temperature in semi-confined space is 552 °C, and the maximum heating rate is 32.1 °C/s. This study is beneficial for the subsequent provision of certain theoretical guidance for LIBs use in semi-confined environments.